Evaluation of final year master’s project course learning outcomes in open university Malaysia - Hazalina Hashim,; Sharifah Rosfashida Syed Abd Latif , (2019)
Learning outcomes are statements on what students should know, understand and can do upon successful completion of a course. Achievement of the learning outcomes is an important criterion for a programme to be awarded with an accreditation qualification by Malaysian Qualifications Agency (MQA). Evidence from teaching and learning evaluation needs to be justified to demonstrate that the learning outcomes have been achieved. In line with this direction, the purpose of this study is to evaluate the learning outcomes of final year master’s project according to course learning outcome and learning domain determined by MQA. This evaluation is carried out by analysing supervisor’s feedback on their supervised student and student feedback themselves. The survey instruments were administered for postgraduate learners in the academic session of 2018, measuring to what extent that course completion has met the learning outcomes and fulfil the learning domain skills required. To strengthen the evidence, result obtained from master’s project report awarded by supervisors and reviewers were compared according to report chapters, programme and learning outcomes perceived. The findings were discussed to highlight the concern, strength and weakness from the evaluation made. Several recommendations for continuous improvement and support were proposed to influence the quality of the course and achievement of the learning outcomes.